Enhanced dust removal via the synergy of a standing wave acoustic field and high-pressure spray: An integrated experimental and numerical study - Shixian Wu; Hui Zhu; Can Qi; Yongping Chen; Hui Yang; Chunyu Liu; Shiqiang Chen; Heqing Liu (PLoS ONE, 2026)
Occupational exposure to respirable coal dust poses severe health risks in underground mining operations, primarily through the development of coal workers’ pneumoconiosis (CWP)—a progressive and irreversible pulmonary disease. To address this challenge, we developed an innovative dust suppression system that integrates ultrasonic atomization with acoustic agglomeration technology. The system operates via a dual-phase mechanism: ultrasonic atomization generates ultrafine water droplets (<10 μm) to form a heterogeneous dust-droplet dispersion, while high-frequency standing wave fields (20 kHz) concentrate airborne particles spatially, thereby enhancing interphase collisions between droplets and dust. The resulting agglomerates are subsequently removed by a high-pressure spray. System performance was systematically evaluated through scaled laboratory experiments that examined three critical operational parameters: nozzle orifice diameter (0.4–0.8 mm) of the high-pressure spray system, acoustic power density (60–180 W) utilized to generate the standing wave field, and duct airflow velocity (0.25–0.75 m/s). Numerical simulations integrating acoustic dynamics with CFD-DEM modeling were employed to elucidate particle trajectories and the spatiotemporal evolution of dust-droplet agglomerates within the coupled acoustic-flow field. Experimental results demonstrate a greater than 10% improvement in PM 2.5 removal efficiency compared to conventional high-pressure spray systems. This enhancement is attributed to the synergistic effects of acoustic focusing and droplet entrapment. The study establishes a foundational framework for the development of acoustically enhanced pretreatment systems and offers a practical strategy for reducing respirable dust exposure in underground mining environments.